2008
DOI: 10.2214/ajr.07.2858
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Embolism Outcome: A Prospective Evaluation of CT Pulmonary Angiographic Clot Burden Score and ECG Score

Abstract: No statistically significant association was seen between ECG score and CT pulmonary angiographic clot burden at diagnosis and the 12-month all-cause mortality rate of patients diagnosed with pulmonary embolism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 32 publications
2
38
0
1
Order By: Relevance
“…Acute pulmonary embolism (PE) is a common and potentially fatal disease with mortality ranging from 2% to 7%, even when treated with anticoagulation (1). Rapid risk assessment is essential in selecting the appropriate treatment strategy in patients with acute PE because high-risk patients may benefit from thrombolysis or embolectomy in addition to anticoagulation.…”
Section: Introductionmentioning
confidence: 99%
“…Acute pulmonary embolism (PE) is a common and potentially fatal disease with mortality ranging from 2% to 7%, even when treated with anticoagulation (1). Rapid risk assessment is essential in selecting the appropriate treatment strategy in patients with acute PE because high-risk patients may benefit from thrombolysis or embolectomy in addition to anticoagulation.…”
Section: Introductionmentioning
confidence: 99%
“…[222324] Earlier retrospective studies have identified the clot burden score to be predictive of short-term mortality. Van der Meer reported 11–fold increase risk of dying within 3 months, if the obstruction index was 40% or higher.…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17] On the other hand, large thrombus burden (as measured by percentage or semi-quantitative indices such as Mastora or Qanadli) does not appear to correlate well with adverse outcomes. [18][19][20] While the criteria for stratification and therefore treatment escalation at present are based upon hemodynamics and RV function, central location of thrombus may be another factor that prompts intervention because thrombus location plays a role in patient selection for catheter-directed therapy and surgical embolectomy.…”
Section: Question 1: Should Submassive Pe Patients Be Treated With Symentioning
confidence: 99%